The real-world effectiveness of vedolizumab on intestinal and articular outcomes in inflammatory bowel diseases. Issue 7 (July 2018) - Macaluso, Fabio Salvatore; Orlando, Rosalba; Fries, Walter; Scolaro, Mariangela; Magnano, Antonio; Pluchino, Dario; Cappello, Maria; Morreale, Gaetano Cristian; Siringo, Sebastiano; Privitera, Antonino Carlo; Ferracane, Concetta; Belluardo, Nunzio; et al.
Abstract: Background: The effectiveness of vedolizumab in real-world practice is under evaluation, while its role in inflammatory bowel disease-associated spondyloarthritis is still unclear. Aims: To report real-world data about the effectiveness of vedolizumab on intestinal and articular symptoms after 10 and 22 weeks of treatment. Methods: Web-based data from the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD) were extracted to perform a prospective multicentre observational study. Results: 163 patients (84 with Crohn's disease and 79 with ulcerative colitis) were included. At week 10, a steroid-free remission was achieved in 71 patients (43.6%), while at week 22 a steroid-free remission was obtained in 40.8% of patients. A response on articular symptoms was reported after 10 weeks of treatment in 17 out of 43 (39.5%) patients with active spondyloarthritis at baseline, and in 10 out of 22 (45.4%) patients at week 22. The only factor associated with articular response was the coexistence of clinical benefit on intestinal symptoms (at week 10: OR 8.471, p  = 0.05; at week 22: OR 5.600, p  = 0.08). Conclusions: Vedolizumab showed good effectiveness after 10 and 22 weeks of treatment. A subset of patients reported improvement also on articular symptoms, probably as a consequence of the concomitant control of gut inflammation.